PHYSICAL PROPERTIES AND RATE OF DIFFUSION TRANSETHOSOME CURCUMIN USING A COMBINATION OF TWEEN 60 AND SPAN 60 AS SURFACTANT - AMALIA, ANISA; SRIFIANA, YUDI; ANWAR, AMALIA (International Journal of Applied Pharmaceutics, 2021)
Objective: Curcumin penetration can be increased by formulating it into the transethosome system. Surfactant is one of the transethosome components that affect the physical properties and penetration of vesicles. In this study, a combination of two surfactants was used to see the effect of surfactants on physical properties and curcumin penetration. Methods: This study used a combination of tween 60 and span 60 with a concentration ratio of 0:5 (F1), 1:1 (F2), 2:1 (F3), and 1:2 (F4). An evaluation included testing the distribution of particle size, zeta potential, and entrapment efficiency in the system. Evaluation continued with the determination of the diffusion rate in vitro. Results: The transethosome system formed has a particle size of 167.9±4.7 nm-396±3.7 nm with a potential zeta value (-) 49.54±1.77 mV-(-) 59.05±0.95 mV, polydispersion index 0.0%-57.1% and entrapment efficiency of 83.76%-93.75%. The diffusion rate of F1 and F3 followed the Higuchi kinetics model, while F2 and F4 followed zero-order kinetics and the Korsmeyer-Peppas kinetics. Conclusion: The combination of tween 60 and span 60 could form a nano-sized transethosome of curcumin. Diffusion rate testing results show that using a surfactant combination can increase the diffusion rate of curcumin, where there is a significant difference between each formula (p<0.05).